PENGARUH PROGRAM REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI PT POS INDONESIA (PERSERO) KANTOR POS DC CIPUTAT - Rini Antika; ratna sari (Jurnal Nusa Manajemen, 2026)
This study aims to determine the effect of Reward and Punishment programs on employee performance at PT Pos Indonesia (Persero) Ciputat Post Office. The method used was quantitative. The sampling technique used probability sampling, resulting in a sample of 56 respondents. Data analysis methods used in the study included instrument testing (validity and reliability), classical assumption tests (normality, multicollinearity, and heteroscedasticity), and simple and multiple linear regression analysis. In addition, correlation coefficient tests, determination coefficient tests (R²), t-tests (partial), and F-tests (simultaneous) were conducted. The results of this study indicate that Rewards have a positive and significant effect on employee performance (t_calculated > t_table or (18.175 > 1.978) with a significance value of 0.000 < 0.05). Punishment has a positive and significant influence on employee performance with a calculated t value > t table or (13.467 < 1.978) with a significance value of 0.001 < 0.05. Reward and Punishment have a positive and significant influence on employee performance with a calculated F value > F table or (53.777 > 3.10) with a significance value of 0.000 < 0.05. Reward and Punishment have a regression effect on employee performance Y = -5.358 + 0.761X1 + 0.345X2. The R-square value (coefficient of determination) is 88.1%, while the remaining 11.9% is influenced by other factors or variables not examined in this study.